Deconstructing the Relationship Between Corporate Social and Financial Performance - Perrini, Francesco; Russo, Angeloantonio; Tencati, Antonio 1968-; Vurro, Clodia (2011)
For four decades, research on the role and responsibilities of business in society has centered on the business case for corporate social responsibility (CSR) and an increasing number of studies on the corporate social performance (CSP)—corporate financial performance (CFP) link emerged leading to controversial results. Heeding the call for a deeper understanding of the mechanisms linking certain CSR efforts to certain performance outcomes, this study provides a stakeholder-based organizing framework rooted in an extensive review of existing literature on the link between CSP and CFP. In so doing, we aim at guiding research and practice toward less simplistic understandings of the CSP–CFP connection, thus advancing the debate over the consequences of voluntary integrating CSR into business operations and into relationships with stakeholders. By disentangling specific drivers and outcomes of the CSP–CFP link, we underline the importance of setting clear boundaries and specifying levels of analysis to generate comparable results.
Keywords: Stakeholder Theory; Multiple bottom line; CSP–CFP link; Corporate Social Responsibility; Corporate Social Performance